2020
DOI: 10.1371/journal.pone.0241961
|View full text |Cite
|
Sign up to set email alerts
|

Breast self-examination practice and associated factors among female healthcare workers in Ethiopia: A systematic review and meta-analysis

Abstract: Background Breast cancer is common global public health problem. It is the principal cause of cancer related death. In Ethiopia, study findings regarding prevalence and associated factors of BSE among female healthcare workers have been inconsistently reported and highly variable. Thus, this systematic review and meta-analysis aimed to determine the pooled prevalence of breast self-examination practice and determinants in Ethiopia. Methods A systematic search of PubMed, Medline, EMBASE, Global Health, Google… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
26
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 51 publications
9
26
2
4
Order By: Relevance
“…The current study revealed that the odds of having good practice of BSE were 7.14 times higher among students with family history of BC than those who had no. This finding is also supported by previous studies [ 14 , 15 , 29 ]. This could be explained by the fact that students having family history of BC are more likely to get the opportunity to notice the burden as well as the preventive and screening measures of BC including BSE than their counters.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The current study revealed that the odds of having good practice of BSE were 7.14 times higher among students with family history of BC than those who had no. This finding is also supported by previous studies [ 14 , 15 , 29 ]. This could be explained by the fact that students having family history of BC are more likely to get the opportunity to notice the burden as well as the preventive and screening measures of BC including BSE than their counters.…”
Section: Discussionsupporting
confidence: 93%
“…This finding is in agreement with results reported from studies conducted in India [ 26 ] and Nigeria [ 29 ]. It is also aligned with the findings of local studies done in Addis Ababa [ 27 ], Debre Tabor [ 33 ], Debre Birhan University [ 16 ], and West Shoa [ 34 ] and SR and MA in Ethiopia [ 14 , 15 ]. This might be due to the logic that students with better knowledge on the way how to do, the time when to do, and the purpose why to do BSE are more likely to test their health status by themselves in this particular issue and are likely to be enthused to know the result.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This study also revealed that about 106 (79.7%) healthcare providers had good knowledge about early detection methods of breast cancer. This finding is consistent with the study on Bahirdar University's female students [31] but lower than a study from West Shoa (66.8%) [17], Eritrea (60.6%) [32] and the pooled prevalence estimate in Ethiopia [28]. The difference might be due to the difference in the study participants and study period.…”
Section: Discussionsupporting
confidence: 89%
“…Most breast cancer patients in developing countries suffer very long delays and have high mortality rates [23][24][25][26]. Although healthcare providers are the key for creating awareness about breast cancer and its early detection methods of breast cancer, most studies reported as that there is a gap in the knowledge and practice of those early detection methods [27][28][29].…”
Section: Discussionmentioning
confidence: 99%